Cerebrospinal fluid leaks after planned intradural spine surgery: a single-center analysis of 91 cases - Koechlin, Nicolas Olmo; Burkhardt, Jan-Karl; Scherer, Moritz; Krayenbühl, Niklaus; Sarnthein, Johannes; Bernays, René-Ludwig; Bozinov, Oliver (Journal of neurological surgery. Part A, Central European neurosurgery, 2013)
Background and Study Object. A leak-proof dura closure after elective surgery for intradural spinal lesions is important to achieve an uncomplicated postoperative course. Because many different closure techniques and dura substitutes exist, we tried to identify the superior material and technique to avoid cerebrospinal fluid leaks (CSFLs). Patients and Methods. Between 2004 and 2009, 91 patients underwent surgical treatment of intradural spinal pathologies with primary dura closure with or without the use of dura substitutes at our institution. Pre- and postoperative images and the clinical course were analyzed retrospectively with respect to the occurrence of CSFL. Results. In 34% of the 91 patients, radiological signs of CSFL were observed. A total of 12 patients (13%) were symptomatic for CSFL and required a single puncture, lumbar drain, or surgical revision. No significant relation between CSFL and patient characteristics, underlying diagnosis, localization, or extension was noted. In contrast, the incidence of CSFL was significantly increased if more than one substitute for dura closure was used. The results showed that 41.7% of these patients showed radiological signs of CSFL as compared with 10.4% of patients in which only a single material was used. Conclusion. In our study, none of the applied products appeared to be superior to the others. Surgery with the combined use of multiple dura closure substitutes was associated with the enhanced incidence of postoperative CSFL. However, our findings concerning the various dura sealants could not be used to compare those different materials, due to the great variety of combinations of dura sealants and the retrospective analysis of the data.
Publikationsdatum: 01. August 2012
Gesehen am 16.12.2021